Application of Zero-Valent Iron Nanoparticles for the Removal of Aqueous Co2+ Ions Under Various Experimental Conditions - Üzüm, Çağrı; Shahwan, Talal; Shahwan, Talal; Eroğlu, Ahmet Emin; Eroğlu, Ahmet Emin; Lieberwirth, Ingo; Scott, Thomas B.; Hallam, Keith R. (Elsevier Ltd., 2008)
Nanosized zero-valent iron (nZVI) is increasingly gaining interest as an efficient sorbent for various types of aqueous pollutants. In this study, nZVI was synthesised by the borohydride reduction method, characterised and then examined for the removal of aqueous Co2+ ions over a wide range of concentrations, from 1 to 1000 mg/L. The size of nZVI particles was predominantly within the range of 20–80 nm, and only limited oxidation was observed in samples aged for a period of 2 months. The experiments investigated the effects of V/m ratio, concentration, contact time, repetitive loading, pH and aging on the extent of retardation of Co2+ ions. Iron nanoparticles demonstrated very rapid uptake and large capacity for the removal of Co2+ ions. Effective uptake was observed even after a number of repetitive trials. The extent of Co2+ uptake increased with the increasing pH. X-ray photoelectron spectroscopy (XPS) indicate that the fixation of Co2+ ions takes place through the interaction of these ions with the oxohydroxyl groups on the iron nanoparticle surfaces in addition to spontaneous precipitate formation at high loadings.
Keywords: Nanosized zero-valent iron; Core–shell structure; Co2+